2020
DOI: 10.1007/s11896-020-09406-x
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Well-being in Former Covert and Undercover Police Officers

Abstract: Little is known about the stressors of working in covert and undercover policing roles and the impact these can have on the health and psychological well-being of police officers. Extant literature focuses upon the social impact of undercover and covert policing in a democratic society, especially in relation to policing political groups. Presented here are the results of an exploratory study into the lives of former police officers who have engaged in various forms of covert/undercover policing. Utilising sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…An emerging body of research is, however, concerned to explore the stressors of working in covert and undercover roles, and the consequences these have on the psychological health and well-being of officers. Curran (2021), for example, conducted interviews with former covert officers and found that fear of interpersonal violence was a common stressor. Of particular relevance to us is that Curran also notes that feelings of guilt and shame were occasionally felt by undercover officers 'when the perceived vulnerability of their targets and those on the periphery were described' (ibid, 262; see also Woods, 2016).…”
Section: Theory-methods Symmetrymentioning
confidence: 99%
“…An emerging body of research is, however, concerned to explore the stressors of working in covert and undercover roles, and the consequences these have on the psychological health and well-being of officers. Curran (2021), for example, conducted interviews with former covert officers and found that fear of interpersonal violence was a common stressor. Of particular relevance to us is that Curran also notes that feelings of guilt and shame were occasionally felt by undercover officers 'when the perceived vulnerability of their targets and those on the periphery were described' (ibid, 262; see also Woods, 2016).…”
Section: Theory-methods Symmetrymentioning
confidence: 99%